Anatomical versus functional motor points of selected upper body muscles. Issue 3 (27th July 2017) - Franz, Alexander; Klaas, Joschua; Schumann, Moritz; Frankewitsch, Thomas; Filler, Timm J.; Behringer, Michael
ABSTRACT: Introduction: In this study we aimed to identify nerve entry points (NEPs) of superficial skeletal muscles obtained by dissection of 20 human cadavers and compared them with motor points (MP) obtained previously by electrical stimulation. Methods: The biceps brachii (BB), trapezius (TZ), latissimus dorsi (LD), pectoralis major (Pmaj), and pectoralis minor (Pmin) muscles were dissected from human cadavers. NEP data (mean ± standard deviation) from each muscle were calculated. F ‐tests with Bonferroni corrections were used to compare NEPs and MPs. Results: The number of NEPs was 2 in BB, 1 in Pmin, 4 in TZ, and 3 in LD, whereas the total number in Pmaj varied from 3 to 5. NEPs and MPs were statistically equal only in Pmin and in the descending part of TZ. Discussion: The findings show crucial differences between NEPs and MPs, possibly impacting the effectiveness of several medical treatment strategies. Muscle Nerve 57 : 460–465, 2018